Suraj mukhi sathvin jamat k lia urdu ka guldasta - Ahsaan,Fouzia Farooqi (Karachi: Oxford university press, 2024)
The Oxford Suraj Mukhi Class 7 book is part of the Oxford University Press series designed for middle school students in Pakistan. It follows the national curriculum, offering a variety of subjects, such as Urdu, English, Science, and Social Studies, to encourage academic and personal development in seventh graders. This book contains a mix of short stories, poetry, and essays from classical and modern Urdu literature. It aims to enhance students' language skills, including grammar, vocabulary, and comprehension. The texts also explore cultural, moral, and ethical themes, promoting critical thinking and creativity in writing.
Keywords: Kanwal- textbook